Pediatric Functional Constipation Questionnaire-Parent Report (PedFCQuest-PR): development and validation - Gamarra, Andrea Catherine Quiroz [UNESP] (2022)
Objective: Developing and validating a disease-specific instrument in the Brazilian Portuguese language to assess the Health-Related Quality of Life of children with functional constipation, applied to parents/caregivers. Methods: The process of developing the questionnaire was carried out in the following steps: items generation concerning functional constipation; elaboration of the preliminary questionnaire; assessment by health professionals; identifying problems or inconsistencies by the researchers; improvement of the questions; obtaining a final questionnaire named Pediatric Functional Constipation Questionnaire-Parent Form (PedFCQuest-PR) with 26 questions divided into four domains. Responses options use a Likert scale based on the events of the last four weeks. The process of validation was an observational, cross-sectional study in a sample of 87 parents/caregivers of children from 5 to 15 years of age diagnosed with Functional constipation according to the Rome IV Criteria. The questionnaire was applied simultaneously to the Pediatric Quality of Life Inventory 4.0 (PedsQL TM 4.0) as a control. Results: The questionnaire validation included 87 parents/caregivers. The children's median age was 8.2 years, with a long time of constipation symptoms associated with fecal incontinence in approximately two-thirds. Internal consistency reliability for the Total Scale Score of PedFCQuest-PR by Coefficient Alpha of Cronbach score was 0.86. Convergent and divergent validity of PedFCQuest-PR was demonstrated by correlating the domains of both questionnaires. Conclusion: This study provides evidence that PedFCQuest-PR is a reliable instrument. The results showed a high degree of internal consistency and validity of the instrument for future applications.